2021
DOI: 10.1093/chromsci/bmab043
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Fucoxanthin in Bloom-Forming Macroalgae by HPLC–UV

Abstract: Fucoxanthin is a carotenoid natural product with extensive biological activities and offers a variety of health benefits. Brown algae and diatoms are known producers of this compound as an important component of their light-harvesting complexes. Considering its important function in algal photosynthesis, we assume that the massive biomass from macroalgal blooms is potential bioresources of this compound. Accordingly, a high-performance liquid chromatography–ultra-violet (HPLC–UV) method was developed and valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…What deserves to be mentioned is that fucoxanthin exhibits antioxidant properties even under anoxic conditions (Torregrosa-Crespo et al 2018 ). Although brown seaweed is the main source of fucoxanthin, it also exists in green seaweeds U. prolifera and C. fragile (Li, Feng, et al 2021 ). Siphonaxanthin, a keto-carotenoid has strong anti-tumor activity by reason of the special structure without epoxide or an allenic bond, and its content in green seaweeds such as Umbraulva japonica , Caulerpa lentillifera , and C. fragile constitutes about 0.03 to 0.1% of the dry weight (Sugawara et al 2014 ; Torregrosa-Crespo et al 2018 ).…”
Section: Active Substancementioning
confidence: 99%
“…What deserves to be mentioned is that fucoxanthin exhibits antioxidant properties even under anoxic conditions (Torregrosa-Crespo et al 2018 ). Although brown seaweed is the main source of fucoxanthin, it also exists in green seaweeds U. prolifera and C. fragile (Li, Feng, et al 2021 ). Siphonaxanthin, a keto-carotenoid has strong anti-tumor activity by reason of the special structure without epoxide or an allenic bond, and its content in green seaweeds such as Umbraulva japonica , Caulerpa lentillifera , and C. fragile constitutes about 0.03 to 0.1% of the dry weight (Sugawara et al 2014 ; Torregrosa-Crespo et al 2018 ).…”
Section: Active Substancementioning
confidence: 99%
“…Prior studies have confirmed the effectiveness of microalgae in serving as a source of fucoxanthin, with diatoms exhibiting a goldenbrown hue, attributed to their richness in pigments such as fucoxanthin [6,7]. Fucoxanthin, an essential xanthophyll carotenoid present in both macroalgae and microalgae, possesses significant market worth [8][9][10]. Earlier research indicates that fucoxanthin exhibits a range of pharmacological properties, encompassing antidiabetic, antioxidant, anti-inflammatory, anti-obesity, antimalarial, anticancer, and more [8,11,12].…”
Section: Introductionmentioning
confidence: 99%